PUZZLE AND FLASHCARD EDUCATIONAL MEDIA'S IMPACT ON CHILDREN'S TOOTH ERUPTION KNOWLEDGE - Sari, Nendika Dyah Ayu Murika; Kinanti, Sukma Ayu; Fransisca, Alicia Putri Dhea; Kaswindiarti, Septriyani; Suparno, Nilasary Rochmanita; Kurniawati, Dwi; Hafizi, Ikmal; Fauziyah, Nida Faradisa (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Introduction: The results of the 2018 Basic Health Research (RISKESDAS) survey stated that the prevalence of children's tooth persistence in the mandibula was 66.23%, and in the maxilla it was 33.77%.  The primary factor influencing the process of tooth eruption in children is their attention to dental health. Health promotion using educational game media can improve knowledge about tooth eruption and make it less boring. Educational games for children aged 7–10 years include puzzles and flash cards. The objective is to evaluate the impact of educational media puzzles and flashcards on children's understanding of tooth eruption. Method: This type of research is quasi-experimental with a pretest-posttest design. The study was conducted on 97 children aged 7-10 years at SD Muhammadiyah 16 Karangasem, Laweyan, Surakarta. The study began with a pretest. Small groups of 5-7 children and 1 researcher played the game. Each small group was given puzzle or flashcard media. The game was played every morning for 7 days; on the seventh day, a posttest was conducted. Results: Flashcard pretest scores, flashcard posttest scores, puzzle pretest scores, puzzle posttest scores. Each group's dependent t-test yielded a p-value of 0.000, while the independent t-test yielded p-values of 0.099 and 0.115. Conclusion: Flashcard and puzzle educational media are each effective in increasing children's knowledge about tooth eruption, but there is no significant difference when the two are compared.